A CRITICAL THOUGHT OF INSTRUCTIONAL STRATEGY: DEVELOPING ANALYTICAL CAPABILITY OF AUTOMOTIVE STUDENTS BY MANAGING MORE APPLICABLE MOVIE FRAGMENTS, POWER POINT, AND INTERACTIVE TEST - Agus Riyanto (Premise: Journal of English Education and Applied Linguistics, 2014)
What most sensed about Technical High School (known as SMK) students is their lack of analytical capability. As their nature of academic orientation is aimed at job fullfillment, the students are enhanced to follow Standard Operational Procedure (SOP) without questioning why such SOP should be followed. As for automotive students, they simply following the steps of doing things related to any activities of repairing car and other mechanical work required just because the job will be done well when the procedure completed.  This kind of mentality “following order or SOP” fits to those who only want to be workers not the men who take higher responsibilities. The progress of automotive technology demand on understanding the concept of how some system used in a car. Failure to comprehend to concept will jeopardize the performance of a car. At the same time, the progress of automotive technology is also propelled by the progress of information technology which provides more open resources that can be used to promote the quality of instuctional process.  Realizing that having analysis compentence is terribly important to run higher responsibilites and continuing education to a university, automotive students need to learn how to analyze. To promote this, teacher can use some automotive movies or animations and then chop them into many fragments related to instructional objectives. The way how the teachers arrange and present the fragments can be combined into power point and ended up with an interactive test with different model of methods, strategies, or techniques. Movies, movie cutter application, interactive test Creator ,  paint into fragments can be obtained freely from the internet.The using of movie fragments integrated into power point, arrange the fragment into various strategies, ended up with interactive test will likely focus the students into more realistic understanding toward the concept taught in the classroom. In return the students will be accustomed to analyze each fragment to building comprehension of concept underlying the skill required in automotive work.